Amine compounds post-treatment on formaldehyde emission and properties of urea formaldehyde bonded particleboard - Ghani, Aizat; Ashaari, Zaidon; Hua Lee, Seng; Saifulazry, Syeed; Ahamad, Nabilah; A’tiyah, Fatimah; Li Lee, Chuan (Walter de Gruyter GmbH, 2022)
Post-treatment of particleboards using three types of amine compounds namely ethylamine, methylamine and propylamine, were produced with 8% urea formaldehyde (UF) resin content and were hot-pressed for 270 s at 180 °C was carried out. The amine compounds were applied over the surface of the particleboard surface at rate of 40–60 g/m2, and the formaldehyde emission value from the board was significantly reduced. In general, the findings of the post-treatment application showed that formaldehyde emissions were successfully decreased from 0.70 mg/L to 0.59–0.33 mg/L without having a substantial impact on the particleboard’s other qualities.